I need to find the arc length of ((x^2)/2 -ln(x)/4) from 2 to 4.
Using the arc length formula, I get that L = ∫ds = ∫ sqrt(1+(f'(x))^2) dx =
∫ sqrt (1 + ((x^3)/6 -1/(4x))^2) dx from x=2 to x=4,
but I cannot solve it any further.
I cannot use u-substitution and I have tried using trig-substitution but it does not seem to work either.
The answer given by WolframAlpha is (1/4)(24 +ln(2)) which is correct, but I want to know how it computed that. I understand that the ln(2) part came from ln(4) - ln(2) = ln(4/2) but beyond that I am lost.